Найти x, если:
$$45. \frac{(2,7 - 0,8) \cdot 2\frac{1}{3}}{(5,2 - 1,4) : \frac{3}{7}} + x + 8\frac{9}{11} - \frac{(1,6 + 154,66 : 70,3) : 1,9}{(2\frac{2}{5} - 1,3) : 4,3} = 2,625.$$
Решение:
\(45. \frac{(2,7 - 0,8) \cdot 2\frac{1}{3}}{(5,2 - 1,4) : \frac{3}{7}} + x + 8\frac{9}{11} - \frac{(1,6 + 154,66 : 70,3) : 1,9}{(2\frac{2}{5} - 1,3) : 4,3} = 2,625.\)

Для того, чтобы решить данное уравнение, упростим данное равенство и найдём x:

\(
1) 2,7 - 0,8 = 1,9 = 1\frac{9}{10};
\)

\(
2) 1\frac{9}{10} \cdot 2\frac{1}{3} = \frac{19}{10} \cdot \frac{7}{3} = \frac{19 \cdot 7}{10 \cdot 3} = \frac{133}{30};
\)

\(
3) 5,2 - 1,4 = 3,8 = 3\frac{8}{10} = 3\frac{4}{5};
\)

\(
4) 3\frac{4}{5} : \frac{3}{7} = \frac{19}{5} \cdot \frac{7}{3} = \frac{19 \cdot 7}{5 \cdot 3} = \frac{133}{15};
\)

\(
5) \frac{133}{30} : \frac{133}{15} = \frac{133}{30} \cdot \frac{15}{133} = \frac{133 \cdot 15}{30 \cdot 133} = \frac{1 \cdot 1}{2 \cdot 1} = \frac{1}{2};
\)

\(
6) 154,66 : 70,3 = 2,2;
\)

\(
7) 1,6 + 2,2 = 3,8;
\)

\(
8) 3,8 : 1,9 = 38 : 19 = 2;
\)

\(
9) 2\frac{2}{5} - 1,3 = 2\frac{4}{10} - 1,3 = 2,4 - 1,3 = 1,1;
\)

\(
10) 1,1 : 4,3 = 11 : 43 = \frac{11}{43};
\)

\(
11) 2 : \frac{11}{43} = 2 \cdot \frac{43}{11} = \frac{86}{11} = 7\frac{9}{11};
\)

\(
12) 8\frac{9}{11} - 7\frac{9}{11} = 8 + \frac{9}{11} - 7 - \frac{9}{11} = 8 - 7 + \frac{9 - 9}{11} = 1;
\)

\(
\frac{1}{2} + x + 1 = 2,625
\)

\(
x + 1\frac{1}{2} = 2,625
\)

\(
x + 1\frac{5}{10} = 2,625
\)
x + 1,5 = 2,625
x = 2,625 - 1,5
x = 1,125
\(
x = 1\frac{125}{100}
\)

\(
x = 1\frac{1}{8}
\)
Ответ: \(x = 1\frac{1}{8}\).

Добавить комментарий


Защитный код
Обновить

Возможно, Вам нужно вот это: